2013
DOI: 10.1002/anie.201302479
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple π Stack of Two Perylene Bisimide Tweezers: A Bimolecular Complex with Kinetic Stability

Abstract: Self-assembly: A tweezer-type perylene bisimide (PBI) dyad self-assembles into a defined bimolecular complex composed of a quadruple PBI π stack with remarkable kinetic stability, which is unprecedented for π-stacked dye aggregates (see picture). These persistent supramolecular species are of considerable interest for the elucidation of functional properties of dye aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 55 publications
(47 reference statements)
0
30
0
Order By: Relevance
“…These could be reduced by the addition of what the authors call a chain terminator, a monofunctional ( N ‐methyl)imidazolyl Zn‐porphyrin. In the light of recent developments in manipulating the kinetic stabilities and kinetic pathways in self‐assembled supramolecular complexes and supramolecular polymers, it is interesting to note, that the addition of the chain stopper to the polymers did not lead to instantaneous disassembly . The expected depolymerization and shortening of the polymers based on the comonomer feed ratio was only observed when the di‐ and monofunctional comonomers were premixed in a good solvent preventing self‐assembly, followed by solvent evaporation and re‐assembly in a non‐solvent.…”
Section: End‐capping Of Supramolecular Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…These could be reduced by the addition of what the authors call a chain terminator, a monofunctional ( N ‐methyl)imidazolyl Zn‐porphyrin. In the light of recent developments in manipulating the kinetic stabilities and kinetic pathways in self‐assembled supramolecular complexes and supramolecular polymers, it is interesting to note, that the addition of the chain stopper to the polymers did not lead to instantaneous disassembly . The expected depolymerization and shortening of the polymers based on the comonomer feed ratio was only observed when the di‐ and monofunctional comonomers were premixed in a good solvent preventing self‐assembly, followed by solvent evaporation and re‐assembly in a non‐solvent.…”
Section: End‐capping Of Supramolecular Polymersmentioning
confidence: 99%
“…These could be reduced by the addition of what the authors call a chain terminator, a monofunctional (N-methyl)imidazolyl Znporphyrin. In the light of recent developments in manipulating the kinetic stabilities and kinetic pathways in selfassembled supramolecular complexes [128][129][130][131][132][133][134][135][136] and supramolecular polymers, 22,[30][31][32][33][34][35][36][37][38][39][40][41][42]130,[137][138][139][140][141][142][143][144][145] it is interesting to note, that the addition of the chain stopper to the polymers did not lead to instantaneous disassembly. 127 The expected depolymerization and shortening of the polymers based on the comonomer feed ratio was only observed when the di-and monofunctional comonomers were premixed in a good FIGURE 3 (a) Chemical structures for the bi-and monofunctional phosphine ligands, P(Phe) 2 C 12 (Phe) 2 P and P(Phe) 2 C 12 , in order to prepare palladium(II)-based coordination polymers.…”
mentioning
confidence: 99%
“…[27,28] Würthner and co-workers have reported discrete p stacks in the aggregation of the related family of perylenediimides, based on the foldamer approach. [29][30][31] However,i ts till remains instructive to develop more efficienta nd viable strategies to construct supramolecular discrete p stacksb ased on flexible p frameworks. [32][33][34][35][36][37][38][39] To this end, we soughtt oi ntroduce orthogonal intramolecular p NDI •••p NDI interactions [40][41][42][43] and hydrogen bonding [44,45] to shapef lexible and discrete p stacks in the NDI system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Matile and co‐workers have utilized anion–π interactions to demonstrate anion transport and catalytic activity in naphthalenediimides (NDIs) . Würthner and co‐workers have reported discrete π stacks in the aggregation of the related family of perylenediimides, based on the foldamer approach . However, it still remains instructive to develop more efficient and viable strategies to construct supramolecular discrete π stacks based on flexible π frameworks .…”
Section: Introductionmentioning
confidence: 99%
“…34 However, in these cases, the separation of the monomer and the dimer was not achieved due to the fast interconversion between the monomeric and dimeric forms in solution. Other than Pc derivatives, few examples are known with supramolecular dimers bound by pp interactions with high kinetic stability, such as the hexaperi-hexabenzocoronenes (HBCs) with oligophenylene dendrons reported by Müllen et al 35,36 or a tweezer-type perylene bisimide (PDI) reported by Würthner et al 37 However, to the best of our knowledge, there are no examples of p-stacking molecules whose monomeric and dimeric forms are kinetically well-stabilized to be separated from each other. Hence, in this manuscript, we aimed to provide the rst example of a Pc dimer bound by p-p interactions, which can be isolated from its monomer and handled as a single chemical entity.…”
Section: Introductionmentioning
confidence: 99%